The challenge of performing aerobic exercise in tropical environments: Applied knowledge and perspectives - Hue, O. (International Journal of Sports Physiology and Performance, 2011)
The tropical climate is unique in that the seasons are dominated by the movement of the tropical rain belt, resulting in dry and wet seasons rather than the four-season pattern of changes in temperature and day length seen in other parts of the world. More than 33% of the world population lives in the humid tropics, which are characterized by consistently high monthly temperatures and rainfall that exceeds evapotranspiration for most days of the year. Both the 2014 Football World Cup (in Brazil) and the 2016 Olympic Games (in Rio de Janeiro) will take place in this climate. This review focuses on the effects of the tropical environment on human exercise performance, with a special emphasis on prolonged aerobic exercise, such as swimming, cycling, and running. Some of the data were collected in Guadeloupe, the French West Indies Island where all the French teams will be training for the 2016 Olympic Games. We will first fully define the tropical climate and its effects on performance in these sports. Then we will discuss the types of adaptation that help to enhance performance in this climate, as well as the issues concerning the prescription of adequate training loads. We will conclude with some perspectives for future research.